Algebraic integers of pure sextic extensions - de Andrade, Antonio Aparecido [UNESP]; Facini, Linara Stéfani [UNESP]; Esteves, Livea Cichito [UNESP] (My University, 2022)
Let K = Q(θ), where (Formula Presented), be a pure sextic field with d ≠ 1 a square free integer. In this paper, we characterize completely whether {1, θ,…, θ5} is an integral basis of K or do not. When d ≢ ±1,±17,±10,−15,−11,−7,−3, 5, 13(mod 36) we prove that K has a power integral basis. Furthermore, for the other cases we present an integral basis
Keywords: Algebraic number field; algebraic number integer; pure sextic extension